Effective Information Infrastructures for Collaborative Organizing: The Case of Maasai Mara - Håkonsson, Dorthe Døjbak; Larsen, Erik Reimer; Eskildsen, Jacob Kjær (Organization Science, 2023)
This study focuses on how collaborative organizing is achieved in a natural-resource commons, organized as an actor-oriented structure. In a framed field experiment, teams of Maasai livestock owners played a board game related to sustainable usage and preservation of a commons (in this case, grazing areas). We examine team decisions over time and draw inferences about the difference between two information infrastructures: one that enables learning about the ecosystem and one that enables shared situational awareness. We also examine the effectiveness of these information infrastructures in obtaining sustainable usage and preservation of a commons, finding that participants who are subjected to an information infrastructure that enables shared situational awareness are more effective than those subjected to an information infrastructure that only enables learning about the ecosystem. This, we argue, is because shared situational awareness enables members to address their interdependencies related to both task and knowledge interdependence. In other words, without shared situational awareness, they are less efficient at coordinating their actions, despite sharing collaborative values. Based on our findings, we argue that actor-oriented structures should be designed to include information infrastructures that specifically address members’ interdependencies. Funding: This work was financially supported by the Interacting Minds Centre (IMC). Supplemental Material: The e-companion is available at https://doi.org/10.1287/orsc.2022.1642 .